A Simulation Study on the Impact of Mobility Models on the Network Connectivity, Hop Count and Lifetime of Routes for Ad hoc Networks (Informatica, 2025)
A Simulation Study on the Impact of Mobility Models on the Network Connectivity, Hop Count and Lifetime of Routes for Ad hoc Networks